The Effect of Online Learning on the Fading of the Discipline Character in Primary School Student - Malinda Anggraini; Fauziyyah Nur Aini; Vandy Kurniawan; Sela Mardiana (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
This research is based on online learning which has an effect on the fading discipline character in elementary school students. The aim of this study was to determine the effect of online learning on the fading discipline character in elementary school students during the Covid-19 pandemic. The research method used an ex-post facto quantitative approach. The population of this study were all 5th grade students at SD Negeri Segugus Ahmad Yani, Purwodadi District, Purworejo Regency amounted 171 student. The sample of this study were 5th grade students at Segugus Ahmad Yani Elementary School, Purwodadi Subdistrict, Purworejo Regency amounted 67 students. The data collection technique used in this research is a Likert scale type of questionnaire. The data analysis technique used is t-test and simple linear regression analysis. The results of the study show that there is an effect of online learning on the discipline character of elementary school students. The level of students discipline at SD Negeri Segugus Ahmad Yani obtained value of 39,18 from 67 students. The results of the regression analysis were 0.34, while the results of the t-test obtained a significance of 2.883. Online learning only contributed 11.56% to the fading of the disciplined character of elementary school students during the Covid-19 pandemic. Keywords: Online Learning, Discipline Character, Elementary School Student